Timing and optimization of dietary supplements for recovery and performance - Ivy, J. L. (Journal of Exercise Science & Fitness, 2004)
To recovery from prolonged strenuous exercise, depleted fuel stores must be replenished, damaged tissue must be repaired and training adaptations must be initiated. Critical to these metabolic processes are the type, amount and timing of nutrient intake. Muscle glycogen is an essential fuel for intense exercise, whether the exercise is of an aerobic or anaerobic nature. Glycogen synthesis is a relatively slow process, and therefore the restoration of muscle glycogen requires special considerations when there is limited time between training sessions or competition. These include 1) consume a carbohydrate supplement immediately post exercise, 2) continue to supplement at frequent intervals, and 3) consume approximately 1.2 g carbohydrate·kg-1 body wt·h-1. Maximizing glycogen synthesis with less frequent supplementation and less carbohydrate can be achieved with the addition of protein to the carbohydrate supplement. This will also promote protein synthesis and reduce muscle degradation, thus having the added benefit of stimulating muscle tissue repair and adaptation. In addition, recent research indicates that consuming a carbohydrate/protein supplement immediately after exercise will have a more positive influence on subsequent exercise performance than a carbohydrate supplement.